Does Microcredit Bring the Women into Economic World: Evidence from Bangladesh - Abdul Matin Chowdhury, M; Che Mohd Salleh, M; Alif Rusmita, S; Sucia Sukmaningrum, P (KnE Social Sciences, 2019)
The empowerment, entrepreneurship and education are the most imperative issues among women to develop the country. Micro credit is one of the effective tools to eradicate poverty among poor people through enhancing women empowerment, enhancing the entrepreneurial activities and improving education level for both men and women. It has initiated the schemes to encourage entrepreneurial activities along with developing education level and enhance the women empowerment in the country. The main goal of this research is to inspect the improvement of women empowerment, evaluate the development of entrepreneurship and the education level among micro credit borrowers in Bangladesh. There are two hundred and thirty respondents were participated in this research. The data were analyzed by the descriptive and multiple linear regression analysis. The results found that the women empowerment slightly develops even though it is not significant statistically whereas the entrepreneurship and education are negatively associated with micro credit programs. This research influences the micro credit institutions to develop and focus on the application of loaned amount by borrowers to affect significantly on women empowerment, entrepreneurial activities and education level. Finally, this research is also merits the government to widen the facilities and lessen the hardship on micro credit institutions and encourages the policy in Bangladesh. Keywords: Micro credit, women entrepreneurship, women empowerment, poverty alleviation, Bangladesh